Association of Interleukin-10 Gene Polymorphisms with Ulcerative Colitis - I. V. Zhilin (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
This literature review is devoted to the study of the role of polymorphic variants of the anti-inflammatory interleukin-10 gene (Interleukin-10, IL10) in the etiology and pathogenesis of ulcerative colitis in patients of various ethnic groups.Aim. To generalize the results obtained from electronic databases on the study of the characteristics of the course of ulcerative colitis in patients of different ethnic groups, taking into account the carriage of IL10 gene polymorphisms.Materials and methods. Twenty-five studies were selected, including four meta-analyzes devoted to the  study of associative relationships of single nucleotide polymorphisms (SNPs) of the IL10 gene isolated from  blood samples at positions -592AA/CA, -819CT, -1082АА/GA, and rs3024505 in the development and course of ulcerative colitis.Results. A number of researchers from Europe, Saudi Arabia report an increased incidence of ulcerative colitis among carriers of the IL10-1082AA SNP and a low incidence among carriers of -592AA. Positive associations of IL10-819CT with the prevalence of ulcerative colitis are presented in single reports from Europe, the Middle East and in a number of studies from Asian countries. However, the identified associations, even within the  same population, are often contradictory. Perhaps the discrepancies are due to the ethnic heterogeneity of the groups in the considered cohorts, and therefore it is necessary to continue epidemiological studies with a large sample size in specific geographic areas.